The EFL Students’ Reading Strategies Across Different Reading Academic Texts - Nuzulianti, Nuzulianti (Institut Agama ISlam Negeri Palangka Raya, 2023)
The purpose of this study was to determine the efl student's reading strategy in various reading courses at IAIN Palangka Raya. This study used quantitative methods and a survey design. This research involved 119 fourth and sixth semester students of the English Department of IAIN Palangka Raya. Data collection was carried out using a questionnaire. The findings indicate students' reading strategies with different text types, namely global strategies (mean = 49.48), support strategies (mean = 33.96), and problem-solving strategies (mean = 31.36), in the fourth and sixth semesters of EFL students at the IAIN Palangka Raya Language Education Study Program. If the standard deviation value is changed to a percentage value, the presentation value of the global strategies is 648.71%, the supporting strategy is 466.13%, and the problem solving strategy is 406.46%. It can be concluded that the reading strategy of students with different types of text in the fourth and sixth semesters is the one that uses the most reading strategy, the global strategy, with a total percentage of 648.71%, with greater marketing than those using support strategies and problem solving strategies.